Surveys of economic theory : resource allocation - Royal Economic Society (Great Britain); American Economic Association (London : Macmillan ; New York : St Martin's Press, 1966)
This volume covers: Theories of Decision-Making in Economics and Behavioural Science; Operations Research; Linear Theory; Research on Household Behaviour; Cost-Benefit Analysis: A survey.
Prepared for the American Economic Association and Royal Economic Society.
Volume III; Surveys IX-XIII.
"First published in the American economic review and the Economic journal."
Includes bibliographical references: p. 203-207.
rpm 13/07/2017
Loans
Keywords: Economics; Economic theory